Harmonizing ecosystem services assessments with sustainable development goals: a case study of the Batticaloa Lagoon Watershed, Sri Lanka - Kulasegaram Partheepan; Muneeb M. Musthafa; Thangamani Bhavan; Beniamino Murgante (City, Territory and Architecture)
Abstract By providing continuous and reliable ecosystem services, ecosystems help attain sustainable development goals (SDGs). Trade-offs between environmental conservation and socioeconomic development limit SDG success. Ecosystem services (ES) methods can help solve these problems and accomplish the SDGs. There is a gap in analyzing SDG progress regarding ESs. To fill this gap, we examined the spatial-temporal changes in ecosystem service values (ESV) and SDG scores in the Batticaloa Lagoon Watershed (BLW) over the past 40 years. The study found that the Western region’s ecosystem service values and ES-SDG Index scores were higher than those of the Eastern regions. The drop in total ESV from 917.41 million US dollars per hectare in 1979 to 731.37 million in 2000 is noteworthy. By 2021, food production, erosion management, and water regulation helped it recuperate to 818.62 million US dollars per hectare. Nine environmental services were devalued between 1979 and 2000 due to agriculture, forest, and wetland losses. In contrast, between 2000 and 2021, wooded land, water bodies, and wetlands increased the value of nine ESs. The entire Batticaloa Lagoon ecosystem’s ES-SDG Index score dropped from 32.1 in 1979 to 21.0 in 2000, then recovered to 24.3 by 2021. Based on worldwide regional data, food and water provisioning, climate regulation, nutrient cycling, habitat and biodiversity, and cultural services have primarily affected the ES-SDG Index score. The SDGs assessment emphasizes the importance of prioritizing SDG6, SDG11, and SDG12 to promote interrelated SDGs in the Batticaloa Lagoon watershed and the world. This prioritization aims to help stakeholders understand the region’s progress toward global SDGs.